Didactique de l'écriture, didactique du français : vers la cohérence configurationnelle - Halté, Jean-François (Repères. Recherches en didactique du français langue maternelle, 2002)
The didactics of writing, the didactics of French : towards the configura-tional coherence. Jean-François Halte, CRDF/CELTED, Université de Metz. Very rich, the didactics of writing is composite even heterogeneous. The actual didactic of writing is the point of outcome of the movement of renovation, in its didactical and pedagogical aspects. As it is, it provides at best knowledge for the use of well-trained teachers likely to «potter about » with efficiency. The pedagogy of writing, the implementations of projects and of situations of production have, it seems, more effects on the performances than the didactical knowledge strictly speaking. Multidimensional, the didactic of writing points out a field of heterogeneous preoccupations and never reaches the expected results in terms of know-how. The failure in writing (reading/writing) is always the major failure in the teaching of French. At the time when French as a subject reconfigurates (cf the recent Official Instructions for elementary school) the didactics of writing would gain to outline its knowledge and to organize them in teachable-programmable in the thread of language, text, discourse. At the same time, the didactics of writing should re-equilibrate fundamentally and take paradigmatically into account the fact that writing (literary) of fiction - determining horizons until then - can be no longer the only reference in practice of writing.